2017
DOI: 10.14236/ewic/hci2017.45
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Children About Online Privacy Through Storytelling in an Interactive Comic

Abstract: Children's privacy is put at risk through online sharing of location-based information. We study the effectiveness of an educational interactive comic on improving 11-to 13-year-old children's privacy knowledge and behaviour immediately and one week after reading. Children's privacy knowledge increased after reading either the comic or the text-only control, but the comic promoted superior knowledge retention a week later and was more successful at influencing children's reported privacy behaviour than the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…For example, evaluations of four tabletop games [14,26,67,162] and an e-book created by us [209] similarly concluded that the tools encouraged discussion among players and may even act as a mediator between adults and children [26,162,209]. Children's educational tools should have a strong and engaging narrative [106,209,210], be age appropriate [106,209], provide realistic choices, and offer opportunities for reflection [106].…”
Section: Engagementmentioning
confidence: 99%
“…For example, evaluations of four tabletop games [14,26,67,162] and an e-book created by us [209] similarly concluded that the tools encouraged discussion among players and may even act as a mediator between adults and children [26,162,209]. Children's educational tools should have a strong and engaging narrative [106,209,210], be age appropriate [106,209], provide realistic choices, and offer opportunities for reflection [106].…”
Section: Engagementmentioning
confidence: 99%
“…Basic skills that need to be mastered by students are communication skills (Prabowo & Ariani, 2018). Comics are more effective in retaining the knowledge to communicate verbally obtained by students (Zhang-Kennedy, Baig, & Chiasson, 2017). In line with research (Ariyanto & Laksana, 2019) educational comics are expected to contribute to the world of education.…”
Section: Figure 1 Display Of Teaching Materials Based On Input From Peersmentioning
confidence: 99%
“…Allow Flexibility and Adaptability. Privacy and security threats are constantly evolving [45]. Therefore, educational content should rapidly adapt to changes to communicate recent trends, threats, and best practices.…”
Section: Design Objectivesmentioning
confidence: 99%
“…Educating users about complex privacy and security issues through comics is an accessible educational approach that could reach a variety of audiences and efectively improve their privacy and security awareness [39,45,50]. However, producing high-quality educational comics is a tedious, labor-intensive, and expensive process due to the time, tools, and software needed.…”
Section: Educational Contextsmentioning
confidence: 99%